Toward greater integration of insights from organization theory and supply chain management - Ketchen, David J.; Hult, G. Tomas M. (Journal of Operations Management, 2007)
AbstractOrganization theory (OT) has the potential to offer provocative and helpful wisdom to the field of supply chain management, yet OT's potential has remained largely underdeveloped in the supply chain arena. As a result, enormous opportunities exist to integrate insights from organization theory and supply chain management in order to build understanding of why some supply chains excel while others do not. We preview the contributions toward developing such a synthesis offered by each of the articles contained in this special issue. Collectively, the articles take a significant step toward closing the gap between ‘what we know’ and ‘what we need to know’ about supply chain management.